DOI: 10.32657/10356/62946
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and design of audio class D amplifiers

Abstract: Perhaps most imperatively, design methods to minimize the IMD in Bang-bang CDAs are largely unknown, including the potential trade-offs with other parameters. Simply put, at this juncture, designers design Bang-bang CDAs largely based on intuition (and experience), and an analytical basis for their designs for the IMD is apparently lacking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Because the distance of the two electrodes is too large to maintain a large enough current the charge density of the cathode surface is affected. The excessively small charge density can not meet the needs of the electrodeposition process of the plasma reaction [11] . Therefore the DLC films can not be generated.…”
Section: The Affect Of the Electrode Distance To The Dlc Filmmentioning
confidence: 99%
“…Because the distance of the two electrodes is too large to maintain a large enough current the charge density of the cathode surface is affected. The excessively small charge density can not meet the needs of the electrodeposition process of the plasma reaction [11] . Therefore the DLC films can not be generated.…”
Section: The Affect Of the Electrode Distance To The Dlc Filmmentioning
confidence: 99%
“…Trivedi et al [6] also studied the transient pressure changes of high head Francis turbine during start-up and shut-down, and found that the pressure changes on the runner are different under different start-up and shut-down strategies, in which the fast start-up and shut-down is 1.5 times of the slow start-up and shut-down. Gou et al [7] predicted the runaway transition process of pumped storage full flow system during power failure, and found that under runaway condition, the pressure at the inlet of volute and draft tube fluctuates periodically at low frequency, with the dominant frequency of 0.27 times runaway frequency.…”
Section: Introductionmentioning
confidence: 99%
“…SiGe/Si dual Fin is considered as next candidate for metal-oxide semiconductor fieldeffect transistor (MOSFET) in advanced node, which fulfills scaling-down requirement. Except of Fin pitch and contact-to-poly pitch scaling-down, device performance can be enhanced by introduction of Ge into PMOS Si [1][2][3][4][5], which shows significant increase of hole mobility, easier Vt engineering and better negative-bias temperature instability (NBTI) than Si. However, SiGe suffers more oxidized consumption during integration processes, Ge self-diffusion, N-P boundary critical dimension (CD) and profile loading via dual Fin plasma etch, Fin CD dependent strain relaxation variation, and threading dislocation defect for SiGe [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%